2018
DOI: 10.3762/bjnano.9.78
|View full text |Cite
|
Sign up to set email alerts
|

Towards the third dimension in direct electron beam writing of silver

Abstract: Carboxylates constitute an extremely promising class of precursor compounds for the electron beam induced deposition of silver. In this work both silver 2,2-dimethylbutyrate and silver pentafluoropropionate were investigated with respect to their dwell-time-dependent deposition behavior and growth characteristics. While silver 2,2-dimethylbutyrate showed a strong depletion in the center of the impinging electron beam profile hindering any vertical growth, silver pentafluoropropionate indicated a pronounced dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 30 publications
(47 reference statements)
1
28
0
Order By: Relevance
“…With a few exceptions [8,24,[68][69][70][71][72][73][74], FEBID materials notoriously suffer from high levels of contaminants (usually carbon) due to incomplete precursor molecule dissociation. The contamination accumulates as partially dissociated molecular fragments become incorporated in the deposit.…”
Section: Materials and Functionalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With a few exceptions [8,24,[68][69][70][71][72][73][74], FEBID materials notoriously suffer from high levels of contaminants (usually carbon) due to incomplete precursor molecule dissociation. The contamination accumulates as partially dissociated molecular fragments become incorporated in the deposit.…”
Section: Materials and Functionalitiesmentioning
confidence: 99%
“…Apart from strong autocatalytic growth effects or very low precursor fluxes, there are no real reasons why the fabrication of freestanding structures should not be possible with these precursors. A particularly interesting material for plasmonic applications is silver, which has recently been demonstrated to be 3D compatible [73]. For this special precursor, the authors identified the GIS alignment and proper heating of both the GIS and the substrate, as decisive elements, which currently are in an optimization phase to achieve sub-100 nm, 3D nanostructures via FEBID.…”
Section: Challengesmentioning
confidence: 99%
“…Several recent studies have demonstrated that focused electron beam induced processing (FEBIP) has high potential for the controlled bottom-up fabrication of metallic 3D nanostructures [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Furthermore, the basic processes during FEBIP are understood to more and more detail leading to developments towards more diverse, cleaner and more defined deposits for various potential applications [7,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to identify molecular subunits that can form stable nonreactive and volatile products upon electron–precursor interaction. The carboxylate group is such a subunit [ 12 16 ]. It holds the promise that it may easily fragment to yield thermodynamically stable CO 2 during electron exposure and thus enhance precursor fragmentation.…”
mentioning
confidence: 99%
“…It holds the promise that it may easily fragment to yield thermodynamically stable CO 2 during electron exposure and thus enhance precursor fragmentation. This expectation is met by a novel fluorinated silver carboxylate precursor that yields deposits with so far unprecedented silver content including 3D structures [ 15 16 ]. However, given a favorable structure, even large organic ligands may be removed more easily than previously anticipated, as exemplified by the electron-induced dissociation of benzene–Cr(CO) 3 [ 17 ] and by FEBID using the fluorine-free precursor Cu(tbaoac) 2 [ 18 ].…”
mentioning
confidence: 99%